Differentiation and genetic variability in natural populations of Anopheles (N.) triannulatus (Neiva & Pinto, 1922) of Brazilian Amazonia. - Santos, Joselita Maria M. (2004)
Populations of Anopheles triannulatus from Macapá (AP), Aripuanã (MT), Ji-Paraná (RO), and Manaus-Janauari Lake (AM) were studied using 16 enzymatic loci. The results of the isozyme analysis showed that the population of Macapá presented higher polymorphism (56.3%). The lowest variability was observed in the population of Manaus (p = 25.0; Ho = 0.077 +/- 0.046). The results of Wright's F statistics showed unbalance due to excess of homozygotes (F(is) > F(st)), denoting a certain intrapopulational differentiation. Although the populations are genetically very close (D = 0.003-0.052), the dendrogram separates the populations in two groups: Macapá separated from that of Manaus, Ji-Paraná, and Aripuanã. This result may suggest a reduction in the genic flow, which possibly had some influence in the substructuration of the populations.